The relationship between cholesterol metabolism and mitochondrial function in chronic obstructive pulmonary diseases. Issue 3 (29th July 2022) - Li, Liyang; Wang, Xiangdong
Abstract: With the development of lipidomics, the significance of lipid metabolism in various lung diseases has been noticed recently. Among them, cholesterol metabolism plays a crucial role in the pathological process of chronic obstructive pulmonary diseases (COPD). Cholesterol accumulation could lead to mitochondrial dysfunction, such as impaired respiration, imbalanced dynamics and decreased adenosine triphosphate production, while mitochondrial dysfunction, especially altered mitochondrial dynamics, could also disrupt lipid homeostasis in cells. This review focuses on cholesterol metabolism and mitochondrial function in COPD and discusses the potential mechanisms of the steroidogenic acute regulatory‐related lipid transfer domain family (STARD), especially STARD3. The review provides new insights for understanding the pathological process between STARD and mitochondria and new therapeutic targets in COPD. Abstract :